Utilization of probiotics for controlling clostridial necrotic enteritis in broiler chickens - Lily Natalia; Adin Priadi (Jurnal Ilmu Ternak dan Veteriner, 2005)
Clostridial necrotic enteritis (CNE) is a common disease among rapidly growing broiler chickens. The purpose of this trial was to study the utilisation of probiotics in controlling experimental CNE in broiler chickens. Chicken normal gut bacterial flora (mucosal starter culture selective/MCS) was used as a competitive exclusion treatment in broiler chicken and its influence to the occurence of clostridial necrotic enteritis were observed. The study comprised of 4 broiler cages treatments of probiotics (2 different dose of MCS, commercial probiotic, 1 cage untreated as control). Probiotics were given orally upon arrival. All groups were given live coccidial vaccine (as predisposing factor for CNE) and challenged with 108 Clostridium perfringens tipe A and C spores on day 10 and 12. The results showed that the probiotics could reduced the incidence and severity of CNE after challenge and improved the performance of chickens treated. Untreated group showed 40% of the mortality due to CNE, and 30% of the chicken showed subclinical necrotic enteritis (SNE).     Key Words: Clostridial Necrotic Enteritis, Probiotics, Broiler Chickeni